2017
DOI: 10.1016/s1470-2045(17)30319-4
|View full text |Cite
|
Sign up to set email alerts
|

Addition of gemcitabine to paclitaxel, epirubicin, and cyclophosphamide adjuvant chemotherapy for women with early-stage breast cancer (tAnGo): final 10-year follow-up of an open-label, randomised, phase 3 trial

Abstract: (2017) Addition of gemcitabine to paclitaxel, epirubicin, and cyclophosphamide adjuvant chemotherapy for women with early-stage breast cancer (tAnGo) : final 10-year follow-up of an open-label, randomised, phase 3 trial. The Lancet Oncology, 18 (6). pp. 755-769. Permanent WRAP URL:http://wrap.warwick.ac.uk/98810 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Chemotherapy remains the important strategy for TNBC treatment following mastectomy, it has elevated a lot in 5 years overall survival rate since it becomes the standard adjuvant therapy for breast cancer. Epirubicin, taxol and cyclophosphamide compose the first line of chemotherapeutics recommended by the guideline [ 17 ]. Nevertheless, drug resistance in TNBC is the major obstacle to a successful outcome following chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy remains the important strategy for TNBC treatment following mastectomy, it has elevated a lot in 5 years overall survival rate since it becomes the standard adjuvant therapy for breast cancer. Epirubicin, taxol and cyclophosphamide compose the first line of chemotherapeutics recommended by the guideline [ 17 ]. Nevertheless, drug resistance in TNBC is the major obstacle to a successful outcome following chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both regimens were found to be safe, deliverable, and tolerable based on toxicity profile, dose intensity and a detailed safety substudy. The results indicated that addition of gemcitabine to anthracycline and taxane-based adjuvant chemotherapy at the dose and schedule of the trial did not confer a therapeutic advantage in terms of disease-free survival in EBC, although it could result in increased toxicity [90].…”
Section: Therapeutic Combinations In Breast Cancermentioning
confidence: 99%
“…Trials investigating newer cytotoxic agents for breast cancer have not yet identified any classes that are clearly superior to taxanes and anthracyclines,2, 3, 4 but the optimal dosage and timing of these two drugs is still unclear. Cell biology and cytokinetic modelling suggest that increasing dose intensity (ie, the amount of drug delivered per unit time) 5 could enhance tumour cell kill, reduce tumour regrowth between cycles, and thereby further improve the likelihood of cure 6, 7.…”
Section: Introductionmentioning
confidence: 99%